Gene copy number variation in human and primate evolution - Sikela, James (Henry Stewart Talks, 2010)
Primate evolution, Human characteristics, Molecular mechanisms underling genome evolution, Gene duplication and evolutionary change, Interhominoid cDNA array-based comparative genomic hybridization, Major clusters of hominoid lineage, Primate gene copy number changes, Primate lineage-specific gene copy number variation, Primate aCGH caveats